Предмет: Алгебра,
автор: никита5680
Упростите выражение:
1) (a+5)^2-(4a^2+40a)
2) (4ab-b^2)+2(a-b)^2
3) 3(2a-5b)^2-12(a-b)^2
Ответы
Автор ответа:
0
1)...=а^2+10а+25-4а^2-40а=-3а^2-30а+25
2)...=4аб-б^2+2(а^2-2аб+б^2)=4аб-б^2+2а^2-4аб+б^2=2а^2
3)...=3(4а^2-20аб+25б^2)-12(а^2-2аб+б^2)=12а^2-60аб+75б^2-12а^2+24аб-12б^2=-36аб+63б^2
2)...=4аб-б^2+2(а^2-2аб+б^2)=4аб-б^2+2а^2-4аб+б^2=2а^2
3)...=3(4а^2-20аб+25б^2)-12(а^2-2аб+б^2)=12а^2-60аб+75б^2-12а^2+24аб-12б^2=-36аб+63б^2
Автор ответа:
0
Спасибо
Автор ответа:
0
не за что!)
Похожие вопросы
Предмет: Физика,
автор: eyeueuushshdhxhzna36
Предмет: Русский язык,
автор: mludap
Предмет: Английский язык,
автор: Fuggut
Предмет: Математика,
автор: ltsy